Affect of Disruptive Energy Supply to Different Type of Industrial and Business Players: An Overview of Concepts and Review of Studies From India - Mangat, Harjit Singh; Singh, Harpuneet (International Journal of Industrial Engineering and Management, 2015)
TAn outage is registered whenever the electricity is completely interrupted for a minute or longer. It frequently takes place during a storm or after an accident when power lines are damaged. At other times, power may be off for quite a few days. From time to time the power company turns off the electricity to an area to save power for 1 to 2 hours at a time.The electricity is returned and after that turned off to another area. Time is money for every industrial as well as business player. Even a brief downtime thrive a wave of tension on the shop floor and ultimately put a blow on the profits of industrial and business players. Electricity plays an essential role in modern society, bringing benefits and progress to industrial, commercial, agricultural and residentialsectors. For all human activities, electric power is vital for economic growth and quality of life. Terms and factors which can affect the electricity network and interrupt customers’ supply will be conferred in detail. An endeavor has been made to thoroughly review and discuss the various key definitions, terms and concepts associated to power system reliability. An in depth effort has been carried out to discuss the various causes of power outages. A review of key studies from India related to the impact of power outages on different businesses and industries is done which reveals that economic impacts from these are immense and hence affect the economy of the nation. Article history: Received (16.12.2014); Revised (13.05.2015); Accepted (17.09.2015)